Severe alcohol use and COVID-19: implications for physical and mental health - Calleja-Conde, Javier; Echeverry-Alzate, Víctor; Sánchez-Diez, Sara; Giné, Elena; Bühler, Kora-Mareen (Frontiers in Psychiatry, 2025)
The COVID-19 pandemic has revealed and intensified the vulnerability of individuals with pre-existing medical and behavioral conditions, notably those related to substance use. Among these, chronic alcohol consumption represents a clinically significant, yet often under-addressed, vulnerability factor that may exacerbate both the acute severity and long-term consequences of SARS-CoV-2 infection. This narrative review examines the biological and clinical intersections between alcohol use and COVID-19, focusing on shared mechanisms of immune dysfunction, neuroinflammation, and disruption of the gut–brain axis. We synthesize current findings showing that both conditions compromise innate and adaptive immune responses, alter cytokine signaling, and weaken mucosal and blood–brain barriers. These changes contribute to cognitive and emotional dysregulation and may increase the risk of persistent neuropsychiatric symptoms, including those observed in Long COVID. In addition, we discuss how chronic alcohol use may alter host susceptibility to infection and affect the immune response to vaccination, with implications for treatment outcomes and recovery. Our findings highlight the need to integrate alcohol use disorder into COVID-19 risk assessments, clinical management, and long-term mental health care planning. A multidisciplinary approach is essential to address the overlapping biological pathways that link alcohol-related vulnerability to COVID-19 outcomes.